(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Molecular biology methods are advocated for specific and accurate diagnosis of parasites. We examined gobiid fishes, Bostrychus africanus and Periophthalmus papilio, from four locations in Rivers State, Nigeria, for parasite identification using molecular biology techniques. Basket traps were used to capture the fish; gobiids were identified using specific guides, and meristic measurements were taken. Parasite isolation was done using standard procedures. The parasites were sorted based on morphological differences by wet microscopy, stored in absolute ethanol and transported to the Regional Centre for Biotechnology and Bioresources Research (RCBBR), University of Port Harcourt, for molecular identification. Two parasites were isolated: an acanthocephalan, which could not be sequenced due to an inadequate amount of DNA (<0.2mol), and ascaridoid nematodes identified using the NCBI database as Baylisascaris transfuga (accession number PV400747; with 97.0% similarity). Prevalence of B. transfuga and the acanthocephalan in B. africanus was 2.0% and 3.3%, respectively. In P. papilio, the prevalence of B. transfuga was 2.4% to 17.9%, while the Acanthocephalan had a prevalence of 17.1%. The gobiids are accidental hosts for B. transfuga, whose definitive hosts are bears. The parasite might have been a subspecies infective to non-bear carnivores in Port Harcourt Zoo. Research gaps include the examination of the zoo animals for the presence of B. transfuga.